2001
DOI: 10.1002/1521-4095(200105)13:10<760::aid-adma760>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Random Lasing in π-Conjugated Films and Infiltrated Opals

Abstract: The properties of random lasers in π‐conjugated polymer films and solutions infiltrated into opal photonic crystals are reviewed. We show that random lasing is a generic phenomenon that occurs in disordered gain media at an excitation intensity regime higher than that giving rise to amplified spontaneous emission. The emission radiation is coherent as demonstrated by photon statistics methods, and its spectrum contains many laser modes from which a typical cavity length can be obtained using Fourier transform … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
105
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 167 publications
(111 citation statements)
references
References 20 publications
(35 reference statements)
2
105
0
1
Order By: Relevance
“…However, more recent experiments showed that narrow emission spikes arise in nearly the entire range of accessible scattering strengths, i.e. for strong, diffusive, and weak scattering [9][10][11]. The key parameters discerning among the three mentioned regimes are the transport mean-free path l t , over which the direction of light propagation is randomized, the size of the sample L, and the wavelength of the light [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, more recent experiments showed that narrow emission spikes arise in nearly the entire range of accessible scattering strengths, i.e. for strong, diffusive, and weak scattering [9][10][11]. The key parameters discerning among the three mentioned regimes are the transport mean-free path l t , over which the direction of light propagation is randomized, the size of the sample L, and the wavelength of the light [12].…”
Section: Introductionmentioning
confidence: 99%
“…By contrast, self-assembly would offer a promising alternative, in which the spontaneous association of microscopic building blocks leads to the energy-free creation of the desired structure. To date, self-assembled threedimensional photonic crystals of conjugated polymers have been realized in inverse configuration only; they are formed by selfassembling particles, made from passive dielectric materials such as silica or polystyrene, into colloidal crystals, backfilling the interstitial spaces with the conjugated polymer and subsequent removal of the colloidal template 5,10 . Ideally however, such photonic devices are prepared through self-assembly alone, without further expenditure of energy or the necessity of costly postprocessing steps.…”
mentioning
confidence: 99%
“…Processability of the active materials is obviously crucial to their incorporation into organic PhC, and, interestingly, water-soluble conjugated polymers with high photoluminescence (PL) efficiency provide an intriguing opportunity for use in combination with plastic PhC templates, but only a few attempts have been reported so far. [19][20][21][22] Conjugated polyelectrolytic rotaxanes 23 ( Fig. 1) offer a very interesting class of materials to incorporate into PhCs since they benefit from a supramolecular architecture in which conjugated backbones such as poly(4,4 -diphenylene vinylene) (PDV) are threaded through cyclodextrin rings (β-CD), that sterically impose increased intermolecular distances.…”
mentioning
confidence: 99%